Potential application of geopolymers in the immobilization of heavy metals: A decade in review (Research, Society and Development, 2023)
Reducing the carbon footprint of building materials can be exploited by recycling mining by-products into different applications, which will preserve natural resources and lessen environmental problems. The bibliometric review aims to summarize the main studies on geopolymers, using geopolymerization as a form of immobilization/solidification and adsorption of heavy metals contained in these residues. With the intention of technical feasibility, a bibliometric review of the literature published between 2011 and 2020 was carried out to critically analyze the structural chemistry, synthesis and environmental applications of geopolymers and to exhaustively discuss the experimental results. The aim is also to critically evaluate the different isothermal and kinetic models to illustrate the mechanisms for effective waste management strategies of different geopolymer binders by thermodynamic spontaneous, endothermic and entropy driven metal trapping process. Emphasizing that the process of immobilization/solidification and adsorption of heavy metals are completely different processes. It presents 86 studies of precursors used for the production of geopolymeric cement, such as metakaolin, blast furnace slag, fly ash and mining residue, including kaolin, aluminum, iron and manganese. The refinement of these articles occurred through the Scopus, VOSviewer and Mendeley platform. To get to the issues that need further investigation, therefore, it has been determined that the issue of “immobilization” needs more attention. Existing studies have revealed the excellent mechanical properties and durability of concretes, mortars and geopolymeric pastes and have predicted their wide application perspective in the field of heavy metal retention.